Adult circumcision and male sexual health: a retrospective analysis. (20th April 2013) - Dias, J.; Freitas, R.; Amorim, R.; Espiridião, P.; Xambre, L.; Ferraz, L.
Summary We aimed to evaluate possible associations of circumcision with several sexual dysfunctions and to identify predictors for the development of these outcomes post‐operatively. Telephone surveys about sexual habits and dysfunctions before and after intervention were conducted post‐operatively to patients that underwent circumcision in Centro Hospitalar Vila Nova de Gaia/Espinho during 2011. McNemar test was used for a matched‐pairs analysis of pre‐ and post‐operative data. Odds ratios, adjusted in a multivariate analysis, explored predictors of de novo sexual dysfunctions after circumcision. With intervention, there was an increase in frequency of erectile dysfunction (9.7% versus 25.8%, P = 0.002) and delayed orgasm (11.3% versus 48.4%, P < 0.001), and a significant symptomatic improvement in patients with pain with intercourse (50.0% versus 6.5%, P < 0.001). Significant predictors for de novo erectile dysfunction were diabetes mellitus (OR 9.81, P = 0.048) and lack of sexual desire (OR 8.76, P = 0.028). Less than three sex partners (OR 7.04, P = 0.007) and low sexual desire (OR 7.49, P = 0.029) were significant predictors for de novo delayed orgasm.